On folding of fuzzy dynamical chaotic manifold - Attiya, H.I.; Radwan, S. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we introduce some types of fuzzy dynamical chaotic manifold .We will also introduce a new type of folding, which is applied to fuzzy dynamical chaotic manifold and we will study the relation between the geometric folding and the chaotic folding of fuzzy dynamical chaotic manifold into itself. And the fuzzy dynamical chaotic manifold will be an achieved deduced.